A Novel Approach to Align Adult Neural Stem Cells on Micropatterned Conduits for Peripheral Nerve Regeneration: A Feasibility Study - Hsu, Shan-hui; Su, Chien-Hsiang; Chiu, Ing-Ming (Artificial organs, 2009)
There is a strong need for nerve‐tissue engineering using the guide conduit and Schwann cells or neural stem cells (NSCs) with regeneration potential for injured peripheral nerves. In this study, micropatterned poly(d,l‐lactide) (PLA) conduits were fabricated by microlithography and solvent‐casting. The PLA conduits were seeded with the novel green fluorescent protein (GFP)‐positive adult mouse NSCs obtained using the patented method of one of the authors. About 85% of the seeded NSCs were successfully aligned on the micropatterned conduits within 72 h and expressed the genes related to the production of neurotrophic factors. Gene expressions for the neurotrophic factors, such as nerve growth factor and brain‐derived neurotrophic factor were upregulated by the micropatterned conduits at 72 h. The micropatterned PLA conduits seeded with the aligned NSCs were used to bridge the 10‐mm sciatic nerve gaps in rats and were found to facilitate nerve repair and functional recovery during a period of 6 weeks compared with the nonseeded group. This model can be used to study the role of adult NSCs in peripheral‐nerve regeneration in the future.